Wirkung der weltweiten Wirtschaftsflaute in den MOEL begrenzt; European Transition Economies World-wide Slowdown of Growth of Limited Impact - Josef Pöschl (The Vienna Institute for International Economic Studies (wiiw), 2002)
Wirkung der weltweiten Wirtschaftsflaute in den MOEL begrenzt Die Abschwächung der Weltkonjunktur, die sich im IV. Quartal 2001 verschärfte, hinterließ auch in den MOEL deutliche Spuren. Die Wachstumsdämpfung blieb allerdings mäßig, die Region erscheint gegenüber dem externen Konjunkturschock relativ widerstandsfähig. In den einzelnen Ländern hatten neben äußeren Einflüssen spezifische interne Entwicklungen großen Einfluß auf das Wirtschaftswachstum. Die Inflation ist weiterhin höher als in den westlichen Industrieländern, hat aber in den meisten Ländern der Region sinkende Tendenz. Die Arbeitslosenquote hat sich auf relative hohem Niveau stabilisiert. Der Außenhandel ist, sieht man von wichtigen Ausnahmen ab, strukturell defizitär. In allen Ländern der Region erscheint das marktwirtschaftliche System fest etabliert. Gleichzeitig besteht, wenn auch in sehr unterschiedlichem Maße, bezüglich der technologischen und institutionellen Ausstattung ein Entwicklungsrückstand. – – In all European transition economies discussed in this article, the GDP grew in both 2000 and 2001. The only exception was Macedonia in 2001, due to a serious political crisis. In those countries that in the past decade experienced an extremely severe economic setback - Bulgaria, Romania, Russia, Ukraine and Yugoslavia - the growth rate jumped to between 5 and 10 per cent at least in one of these two years. In 2002, almost all countries will be unable to achieve a growth rate similar tot that reported in 2000-01. The world-wide slowdown of economic growth, and especially the growth deceleration in Germany and other EU countries, has shown a direct impact on the export performance of transition countries exports grew only insignificantly in the last months of 2001, and the same was true for industrial output. GDP growth was low in the first quarter of 2002, however is likely to intensify in the course of the year as well as in 2003. The inflation rate has become one-digit in most of the countries; a trend towards nominal appreciation emerged in some of the leading countries. A more rapid introduction of the euro is likely to become a hot topic in the course of EU accession. Austria is making a comfortable surplus in its trade with the Central European transition countries, and especially with Hungary, Croatia, and Slovenia. Hungary is also Austria's major business partner in the region.
Additional information: Reprint from: WIFO-Monatsberichte, Vol. 75, No. 5, May 2002
Keywords: 330